Hollow silica nanoparticles, methods of making same, and resulting products
By regulating the siloxane hydroxyl content and maturation conditions during the preparation of hollow silica, the problems of hollow silica in aqueous solution and the polycondensation of silicon hydroxyl groups are solved, and the stable dispersion and efficient anti-reflection properties of nanoparticles are achieved.
Patent Information
- Application Number
- CN202411653917.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, hollow silica is unstable and easy to settle in aqueous solution, and the silicon hydroxyl groups with high active sites during maturation will produce their own polycondensation reaction, resulting in unstable dispersion.
By fully mixing the silicone source, surfactant, expansion agent, catalyst and organic solvent, after heating, mineralization reaction is carried out in the presence of a catalyst, hollow silica primary particles are obtained by centrifugation, and the siliceous hydroxyl content is controlled between 16% and 25%, ensuring the stability of the dispersion.
The stable existence of hollow silica nanoparticles is achieved, hard agglomeration or soft agglomeration is avoided, dispersed in the organic system without precipitation, and the particle refractive index is reduced, and the anti-reflection performance of the anti-reflection film is improved.
Smart Images

Figure CN119528160A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material chemistry technology, and in particular to hollow silica nanoparticles, a preparation method thereof and the resulting products. Background Art
[0002] Hollow silica has the advantages of low density, large specific surface area, multiple reaction sites, adjustable cavity space and small size. It has a wide range of applications in absorption, catalysis, energy storage, fluorescence imaging and drug delivery / therapy.
[0003] In future applications, size uniformity is very important because the physical, electrical, magnetic and optical properties of nanoparticles depend largely on their size and uniformity. In addition to the uniformity of the size itself, the silanol group is also required to provide more reaction sites for chemical reactions, thereby obtaining a water-based or organic solvent-based hollow silica dispersion with stable dispersion and no agglomeration. However, if the silanol content is too high, it will produce soft agglomeration when dispersed in an organic system under certain conditions.
[0004] In the patent CN114506849B, a silica precursor is added to water with the aid of a dispersing device, and reacted at 25°C-35°C for 18h-24h to obtain a primary dispersion of hollow silica particles, and then in order to adjust the shell thickness and increase the hollow ratio, the temperature is 180°C-250°C and the reaction time is 12h-24h for aging. The hollow silica aqueous solution needs to be added with an additional particle stabilizer to solve the problem that silica is unstable and easy to precipitate in the aqueous solution, and the problem that the silanol group with higher active sites will produce self-condensation reaction during the aging process is not solved. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a hollow silica nanoparticle, a preparation method thereof and the resulting product.
[0006] The invention provides hollow silicon dioxide nanoparticles, the average hollow rate of the hollow silicon dioxide nanoparticles is 50%-70%, the average particle diameter is 20-80nm, and the percentage of hydroxyl groups on the surface of the nanoparticles is 16%-25%.
[0007] The present invention also provides a method for preparing the above-mentioned hollow silica nanoparticles, comprising the following steps: fully mixing an organic silicon source, a surfactant, an expander, a catalyst, and an organic solvent, and heating the mixture to complete the reaction to obtain a silane polymer solution; in the presence of a catalyst, subjecting the silane polymer solution to a mineralization reaction, and centrifugally washing the mixture to obtain hollow silica primary particles; and then mixing the hollow silica primary particles with water and heating and aging the mixture to obtain a stable and precipitate-free aqueous hollow silica secondary particle dispersion.
[0008] The present invention also provides an anti-reflection film, which is prepared by using the hollow silica nanoparticles or the preparation method.
[0009] The present invention has the following beneficial effects:
[0010] The present invention provides hollow silica nanoparticles, a preparation method thereof and the obtained products. The hollow silica nanoparticles provided by the present invention have a hydroxyl content of 16% to 25% on the surface of the hollow silica nanoparticles, so that the hollow silica nanoparticles can exist stably, are not easy to produce hard agglomeration or soft agglomeration, and do not produce precipitation when dispersed in an organic system. In addition, the low wall thickness and high cavity rate of the hollow silica nanoparticles are conducive to reducing the refractive index of the particles and improving the anti-reflection performance of the anti-reflection film. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0012] Figure 1 TEM image of the hollow silica nanoparticles prepared in Example 1;
[0013] Figure 2 This is the TEM image of the hollow silica nanoparticles prepared in Comparative Example 1. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0015] The present invention provides hollow silica nanoparticles, a preparation method thereof and the obtained products, aiming to solve the problems that the hollow silica surface has high silanol activity, strong polarity, easy dehydration to form Si-O-Si bonds under high temperature and high pressure, affecting the dispersibility and compatibility with organic systems.
[0016] The following is a detailed description of a hollow silica nanoparticle, a preparation method thereof and a product obtained therefrom provided in an embodiment of the present invention.
[0017] In a first aspect, an embodiment of the present invention provides a hollow silica nanoparticle, wherein the average hollow ratio of the hollow silica nanoparticle is 50%-70%, the average particle size is 20-80 nm, and the percentage of hydroxyl groups on the surface of the nanoparticle is 16%-25%.
[0018] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned hollow silica nanoparticles, comprising the following steps: fully mixing an organosilicon source, a surfactant, an expander, a catalyst, and an organic solvent, and heating the mixture to complete the reaction to obtain a silane polymer solution; in the presence of a catalyst, subjecting the silane polymer solution to a mineralization reaction, and centrifuging and washing the mixture to obtain hollow silica primary particles; and then mixing the hollow silica primary particles with water and heating and maturing the mixture to obtain a stable and precipitate-free aqueous hollow silica secondary particle dispersion.
[0019] In some optional embodiments, the method further comprises: post-treating the prepared stable and precipitate-free aqueous hollow silica secondary particle dispersion;
[0020] Preferably, the post-treatment comprises: uniformly mixing a water-based hollow silica secondary particle dispersion, propylene glycol methyl ether acetate and a silane coupling agent, and performing modification at 50-70° C. to obtain a stable and precipitate-free oil-based hollow silica secondary particle dispersion, wherein: the silane coupling agent comprises at least one of 3-(methacryloyloxy)propyltrimethoxysilane, KH570 and KH550;
[0021] Preferably, the post-treatment comprises: separating and washing the aqueous hollow silica secondary particle dispersion, and adjusting the solid content of the dispersion to 5-20% to obtain a hollow silica nanoparticle dispersion;
[0022] Preferably, the post-treatment comprises: drying the aqueous hollow silica secondary particle dispersion to obtain hollow silica nanoparticle powder.
[0023] In the process of modifying the water-based hollow silica secondary particle dispersion into the oil-based hollow silica secondary particle dispersion, a proper amount of silane coupling agent is added. The special structure of the silane coupling agent makes the silane alkoxy reactive to inorganic substances, and the organic functional group reactive or compatible to organic substances. Therefore, when the silane coupling agent is between the inorganic and organic interfaces, a bonding layer of organic matrix-silane coupling agent-inorganic matrix can be formed, so that the water-based hollow silica secondary particle dispersion is smoothly modified into the oil-based hollow silica secondary particle dispersion, and after the oil-based hollow silica secondary particle dispersion is left to stand for a period of time, no precipitation will be generated in the system.
[0024] In some optional embodiments, the silane polymer solution is prepared by the following method: at room temperature, a surfactant, a swelling agent and a catalyst are placed in an organic solvent and stirred evenly to obtain a modifier solution; then an organic silicon source is added to the modifier solution, and after heating and reaction is complete, a silane polymer solution is obtained;
[0025] Preferably, the surfactant has an HLB value of ≥10 and contains one or more hydroxyl groups. Preferably, the surfactant comprises at least one of a hydroxyl-containing triblock polymer and a hydroxyl-containing nonionic surfactant, more preferably at least one of F108, F127, and polyethylene glycol;
[0026] Preferably, the expansion agent includes at least one of toluene and trimethylbenzene;
[0027] Preferably, the catalyst includes at least one of acetic acid, hydrochloric acid, hydrofluoric acid, ammonia water, and sodium hydroxide;
[0028] Preferably, the organic solvent includes at least one of methanol, ethanol, isopropanol, acetone, methyl butyl ketone, methyl isobutyl ketone, and propylene glycol methyl ether acetate;
[0029] Preferably, the organic silicon source includes at least one of tetramethoxysilane, vinyltriethoxysilane, 3-aminopropyltrimethoxysilane and fluorine-containing silane.
[0030] The embodiment of the present invention provides a method for preparing hollow silica nanoparticles, which comprises: firstly, fully mixing an organic silicon source, a surfactant, an expansion agent, a catalyst, and an organic solvent, and heating the mixture to complete the reaction to obtain a silane polymer solution; then, the silane polymer solution is subjected to mineralization and aging to obtain a hollow silica secondary particle dispersion, wherein:
[0031] Surfactant: A substance that can significantly change the interface state of its solution system by adding a small amount, and HLB (hydrophile-lipophile balance) ≥ 10, containing one or more hydroxyl groups. It has fixed hydrophilic and lipophilic groups, can be arranged in a directional manner on the surface of the solution, and must have a hydroxyl functional group. Including but not limited to: triblock polymers (F108, F127), non-ionic surfactants (polyethylene glycol).
[0032] Swelling agent: After the introduction of the swelling agent, the core (hydrophobic part) of the micelle swells. Due to the filling of the swelling agent, the size of the hydrophobic core increases. According to the principle of like-is-compatible, the hydrophobic swelling agent can enter the hydrophobic part inside the single bundle. This may cause the internal hydrophobic part to swell. As the volume of the internal hydrophobic part increases, the size of the single micelle also increases accordingly. The internal core of the hollow silica increases, the surface area of the microspheres increases, and the surface silanol content increases accordingly. The swelling agent and one end of the surfactant meet the principle of like-is-compatible. Including but not limited to: toluene, trimethylbenzene.
[0033] Organic solvent: an organic compound containing carbon atoms. It is liquid at room temperature and pressure, has high volatility, and the properties of the solute and solvent do not change during the dissolution process. Including but not limited to: methanol, ethanol, isopropanol, acetone, methyl butyl ketone, methyl isobutyl ketone, propylene glycol methyl ether acetate.
[0034] Catalyst: A substance that can change (speed up or slow down) the chemical reaction rate of other substances in a chemical reaction, while its own mass and chemical properties do not change before and after the reaction (they will change during the reaction). Including but not limited to: acetic acid, hydrochloric acid, hydrofluoric acid, ammonia water, sodium hydroxide.
[0035] Organic silicon source: Under certain conditions, silicon-containing oligomers are formed by hydrolysis, condensation or other methods. The generated oligomers contain hydroxyl functional groups. Organic silicon sources include but are not limited to: vinyl triethoxysilane, 3-aminopropyl trimethoxysilane, and fluorine-containing silane.
[0036] In some optional embodiments, the heating reaction temperature is 70°C-100°C, and the time is 1h-6h.
[0037] In some optional embodiments, the preparation of hollow silica primary particles includes: removing impurities from the silane polymer solution, mixing it evenly with a dispersant, adding a catalyst to carry out a mineralization reaction, and centrifuging and washing to obtain hollow silica primary particles;
[0038] Preferably, removing impurities from the silane polymer solution comprises: removing impurities generated in the heating reaction from the silane polymer solution by atmospheric distillation or reduced pressure distillation;
[0039] Preferably, the dispersant includes at least one of water, water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide, guar gum, and polyethylene glycol esters of fatty acids;
[0040] Preferably, the catalyst includes at least one of acetic acid, hydrochloric acid, hydrofluoric acid, ammonia water, and sodium hydroxide.
[0041] The embodiment of the present invention provides a method for preparing hollow silica nanoparticles, which comprises: subjecting a silane polymer solution to a mineralization reaction, and centrifugation washing to obtain hollow silica primary particles, wherein: the dispersant used is a surfactant having two opposite properties, lipophilicity and hydrophilicity, in the molecule. Generally, it is divided into two categories: inorganic dispersants and organic dispersants. Commonly used ones include water, water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium dodecyl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide, gum, fatty acid polyethylene glycol esters, etc. Adding a dispersant can make the generated hollow silica primary particles more dispersible and less prone to agglomeration.
[0042] In some optional embodiments, the mass ratio of the silane polymer to the dispersant in the silane polymer solution is 1:30-1:5, and the mass ratio of the silane polymer to the catalyst is 10:1-2:1.
[0043] In some optional embodiments, the preparation of the hollow silica secondary particle dispersion includes: uniformly mixing the hollow silica primary particles and water, and heating and aging to obtain a hollow silica secondary particle dispersion having a surface hydroxyl content of 16%-25%;
[0044] In some optional embodiments, the heating and aging temperature is 150° C.-240° C., and the time is 30 h-40 h.
[0045] The embodiment of the present invention provides a method for preparing hollow silica nanoparticles, which comprises: after preparing hollow silica primary particles using a silane polymer solution, subjecting the silane polymer solution to a mineralization reaction and a maturation reaction to obtain a hollow silica secondary particle dispersion, wherein the excessively high silanol content will produce hard agglomerates when dispersed in an organic system. During the maturation process, when the hydroxyl content is reduced to a certain extent, the hollow silica particles will produce soft agglomerates, and thus a uniform solution cannot be formed after modification. In the present invention, the problem that silanol is easily dehydrated to form Si-O-Si bonds under high temperature and high pressure is solved by regulating the maturation temperature and time, and a dispersion or powder of hollow silica particles with a unit mass percentage of silanol of 16%-25% is prepared, which does not produce precipitation when dispersed in an organic system.
[0046] It can be seen that the embodiment of the present invention provides a method for preparing hollow silica nanoparticles, which includes: first preparing a silane polymer solution, and in the process of preparing the silane polymer solution, adding an organic silicon source to a modifier solution containing a surfactant, a swelling agent and a catalyst, and under the action of the catalyst, the organic silicon source is hydrolyzed, condensed or other methods to form a silicon-containing oligomer, and at the same time, in the polymerization process of the organic silicon source, a swelling agent is introduced to swell the inner core (hydrophobic part) of the micelle. Due to the filling of the swelling agent, the size of the hydrophobic core increases, thereby increasing the size of the generated hollow silica core, increasing the surface area of the microspheres, and increasing the surface silanol content, thereby improving the silanol content on the surface of the hollow silica nanoparticles. Afterwards, the silane polymer solution is subjected to a mineralization reaction, so that the silane polymer can generate primary silica particles, and then by controlling the aging temperature and time, a hollow silica with a hollow ratio of 50%-70%, a particle size of 20-80nm, and a stable and precipitate-free aqueous hollow silica dispersion containing 16%-25% of hydroxyl functional groups outside the shell by mass percentage is prepared. Further, the aqueous hollow silica dispersion can be modified to obtain a stable and precipitate-free oil-based hollow silica nanoparticle dispersion, or the aqueous hollow silica dispersion can be separated and washed, and the solid content of the dispersion is adjusted to obtain an aqueous hollow silica dispersion with a desired solid content, or the aqueous hollow silica dispersion is dried to obtain a hollow silica nanoparticle powder. Hollow silica nanoparticles can exist in a variety of forms, especially when dispersed in water or an organic solvent without precipitation, which greatly improves its application value.
[0047] In a third aspect, an embodiment of the present invention provides an anti-reflection film, wherein the hollow silica nanoparticles are prepared by using the above-mentioned hollow silica nanoparticles or the above-mentioned preparation method.
[0048] The present invention will be further described below in conjunction with the embodiments.
[0049] The silanol content mentioned in this article refers to the mass ratio of hydroxyl groups contained in the sample per unit mass.
[0050] The principle of hydroxyl content is based on the fact that the silanol of silica is a Lewis acid that can undergo ion exchange reaction. Only through this ion exchange mechanism can the acid-base titration method be used to determine the silanol content on the surface of hollow silica. The specific operation of this method is to disperse 1.5g of fumed silica in a 200g / L sodium chloride solution, adjust the solution pH to less than about 3.0, and then titrate with 0.1mol / L NaOH solution. The sodium hydroxide consumed when the solution pH changes from 4.0 to 9.0 is caused by the reaction of silanol with NaOH. Therefore, the amount of sodium hydroxide consumed during this period can be used to calculate the content of silanol. The specific calculation formula is as follows:
[0051]
[0052] The content of silanol groups on the surface of hollow silica nanoparticles, unit: mass percentage (%);
[0053] C NaOH : The exact concentration of NaOH, unit: (mol / L);
[0054] V pH4-9 : The volume of NaOH consumed when the pH value rises from 4.0 to 9.0, unit: milliliter (mL);
[0055] V B : Blank test determination value, unit: milliliter (mL).
[0056] The method for preparing hollow silica nanoparticles comprises the following steps:
[0057] (1) At room temperature, add the surfactant and swelling agent into the organic solvent and stir evenly, then add the catalyst and stir for 4h-6h to obtain the modifier solution.
[0058] (2) Add an organic silicon source to the modifier solution obtained in step (1), raise the temperature to 70° C.-100° C., and stir for 1 h-6 h to obtain a silane polymer solution.
[0059] (3) The silane polymer solution obtained in step (2) is subjected to atmospheric distillation or reduced pressure distillation to remove impurities generated by the above reaction.
[0060] (4) adding the silane polymer solution obtained in step (3) into a dispersant (the mass ratio of the silane polymer to the dispersant in the silane polymer solution is 1:30-1:5) to obtain a white or translucent solution, and then adding a catalyst (the mass ratio of the silane polymer to the catalyst is 10:1-2:1) to carry out a mineralization reaction, and after centrifugal washing, obtaining hollow silica primary particles.
[0061] (5) The hollow silica primary particles obtained in step (4) and water are uniformly mixed and added into a reaction kettle, and heated for aging, wherein the aging temperature is controlled to be 150° C.-240° C. and the aging time is 30 h-40 h, thereby obtaining a hollow silica secondary particle dispersion having a hydroxyl content of 16%-25%;
[0062] (6) Separating and washing the hollow silica secondary particle dispersion obtained in step (5), adjusting the solid content of the dispersion to 5-40%, to obtain a hollow silica nanoparticle dispersion, or drying to obtain a hollow silica nanoparticle powder.
[0063] Example 1
[0064] (1) At 25°C, 12.6 g of triblock poly(ethylene oxide) b-poly(propylene oxide)-b-poly(ethylene oxide) copolymer EO 106 PO 70 EO 106 (Pluronic F127, M w =12600), 9.2 g of toluene was added to 50 g of anhydrous ethanol solution and stirred evenly, then added to 10 g of hydrochloric acid and stirred for 5 h to obtain a modifier solution.
[0065] (2) Add 152 g of tetramethoxysilane to the modifier solution obtained in step (1), raise the temperature to 70° C., and stir for 5 h to obtain a silane polymer solution.
[0066] (3) The silane polymer solution obtained in step (2) is subjected to normal pressure distillation or reduced pressure distillation to remove impurities generated.
[0067] (4) 10 g of the silane polymer solution obtained in step (3) was added to 200 g of water to obtain a white or translucent solution, and then 1 g of ammonia water was added to carry out a mineralization reaction. After centrifugal washing, hollow silica primary particles were obtained.
[0068] (5) The hollow silica primary particles obtained in step (4) and water are uniformly mixed and added into a reaction kettle, and aged at 150° C. for 30 h to obtain a hydroxyl content of The solid content of the aqueous nano hollow silica secondary particle dispersion was adjusted to 20% (hollow ratio of 55%, particle size of 30nm). The transmission electron microscope photo showed that the hydroxyl groups on the particle surface did not undergo self-condensation, so there was no adhesion between the particles. Figure 1 , no precipitation in aqueous solution.
[0069] (6) 150 g of the hollow silica secondary particles obtained in step (5), 100 g of propylene glycol methyl ether acetate, and 2 g of a silane coupling agent (KH550) were mixed evenly, and modified at 50° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 h without precipitation.
[0070] Example 2
[0071] The aging time and temperature in Example 1 were adjusted to 180°C-30h to obtain a hydroxyl content of The transmission electron microscope photo shows that there is no adhesion between the particles.
[0072] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were mixed evenly, modified at 60° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours without precipitation.
[0073] Example 3
[0074] The aging time and temperature in Example 1 were adjusted to 210°C-30h to obtain a hydroxyl content of Nano hollow silica secondary particles (hollow ratio 55%, particle size 70nm). No precipitation in aqueous solution.
[0075] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were mixed evenly, modified at 70° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours without precipitation.
[0076] Example 4
[0077] The aging time and temperature in Example 1 were adjusted to 240°C-30h to obtain a hydroxyl content of Nano hollow silica secondary particles (hollow ratio 70%, particle size 80nm). There is adhesion between particles. There is no precipitation in the aqueous solution.
[0078] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were uniformly mixed and modified at 50 to obtain oily hollow silica. The dispersion was allowed to stand for 4 hours without precipitation.
[0079] Example 5
[0080] The aging time and temperature in Example 1 were adjusted to 180°C-34h to obtain a hydroxyl content of Nano hollow silica secondary particles (hollow ratio 50%, particle size 70nm). No precipitation in aqueous solution.
[0081] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were mixed evenly, modified at 70° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours without precipitation.
[0082] Example 6
[0083] The aging time and temperature in Example 1 were adjusted to 180°C-36h to obtain a hydroxyl content of Nano hollow silica secondary particles (hollowness ratio 65%, particle size 50nm). No precipitation in aqueous solution.
[0084] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were mixed evenly, modified at 60° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours without precipitation.
[0085] Example 7
[0086] The aging time and temperature in Example 1 were adjusted to 180°C-38h to obtain a hydroxyl content of Nano hollow silica secondary particles (hollowness ratio 60%, particle size 40nm). No precipitation in aqueous solution.
[0087] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were mixed evenly, modified at 70° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours without precipitation.
[0088] Example 8
[0089] The aging time and temperature in Example 1 were adjusted to 180°C-40h to obtain a hydroxyl content of Nano hollow silica secondary particles (hollow ratio 55%, particle size 70nm). No precipitation in aqueous solution.
[0090] The hollow silica secondary particles, propylene glycol methyl ether acetate and silane coupling agent were mixed evenly, modified at 50° C. to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours without precipitation.
[0091] Example 9
[0092] The block poly(ethylene oxide) b-poly(propylene oxide)-b-poly(ethylene oxide) copolymer in Example 1 was replaced with polyethylene glycol, and other conditions remained unchanged. The hydroxyl content was obtained. Nano hollow silica secondary particles (hollow ratio 75%, particle size 70nm). No precipitation in aqueous solution.
[0093] After modification, an oil-based hollow silica dispersion was obtained, which was left to stand for 24 hours without precipitation.
[0094] Example 10
[0095] The tetramethoxysilane in Example 1 was replaced with 3-aminopropyltrimethoxysilane, and other conditions remained unchanged. The hydroxyl content was obtained to be Nano hollow silica secondary particles (hollow ratio 45%, particle size 55nm). No precipitation in aqueous solution.
[0096] After modification, an oil-based hollow silica dispersion was obtained, which was left to stand for 24 hours without precipitation.
[0097] Comparative Example 1
[0098] The block poly(ethylene oxide) b-poly(propylene oxide)-b-poly(ethylene oxide) copolymer in Example 1 was replaced with tetra(2-ethylhexyloxy)silane, and other conditions remained unchanged. The hydroxyl content was obtained to be Nano hollow silica secondary particles (hollowness ratio 50%, particle size 40nm). Transmission electron microscope photos show that a large amount of adhesion occurs between the particles. Figure 2 After modification, an oil-based hollow silica dispersion was obtained, which was allowed to stand for 24 hours to produce precipitation.
[0099] Comparative Example 2
[0100] The tetramethoxysilane in Example 1 was replaced with a copolymer of ethylene oxide and propylene oxide, the amount of silane coupling agent was 4 g, and other conditions remained unchanged. The hydroxyl content was obtained to be Nano hollow silica secondary particles (hollow ratio 70%, particle size 65nm). Transmission electron microscope photos show that there is a lot of adhesion between particles. The aqueous solution has precipitation. After modification, an oil-based hollow silica dispersion is obtained, which is left to stand for 24 hours to produce precipitation.
[0101] Comparative Example 3
[0102] Experimental step 5 in Example 1 was omitted, and 150 g of hollow silica primary particles with a hydroxyl content of 27% produced in experimental step 4 (hollowness rate of 50%, particle size of 35 nm), 100 g of propylene glycol methyl ether acetate, and 2 g of silane coupling agent were mixed evenly, modified at 50°C to obtain an oily hollow silica dispersion, which was allowed to stand for 24 hours to produce a precipitate.
[0103] Comparative Example 4
[0104] The aging time and temperature in Example 1 were adjusted to 260° C.-40 h, and other conditions remained unchanged. The hollow silica solution was gelled and could not be modified, and the hollow silica particles were softly agglomerated.
[0105] Comparative Example 5
[0106] The aging time and temperature in Example 1 were adjusted to 220° C.-45 h, and other conditions remained unchanged. The hollow silica solution was gelled and could not be modified, and the hollow silica particles were softly agglomerated.
[0107] Table 1 below shows the hydroxyl content on the surface of the hollow silica nanoparticles obtained in Examples 1-10 and Comparative Examples 1-3, their dispersibility in aqueous solution before modification, and their compatibility with organic solvents (propylene glycol methyl ether acetate) after modification.
[0108] Table 1
[0109]
[0110] From the test results of Examples 1-10 and Comparative Examples 1-3 shown in the table, it can be concluded that the silanol content on the surface of the hollow silica nanoparticles prepared by the method provided in the embodiment of the present invention is 16%-25%, so that the hollow silica nanoparticles can exist stably, are not prone to hard agglomeration or soft agglomeration, and do not produce precipitation when dispersed in an organic system.
[0111] From the comparison of Examples 1, 10 and Comparative Example 1, it can be seen that by changing the type of silicon source, the oligomers formed by hydrolysis and condensation do not contain hydroxyl groups, the prepared hollow silica particles have a low hydroxyl content, and precipitation occurs in the aqueous phase. The modified hollow silica has poor compatibility with organic solvents and produces precipitation.
[0112] From the comparison of Examples 1, 9 and Comparative Example 2, it can be seen that the surfactant does not contain hydroxyl groups, the prepared hollow silica particles have a low hydroxyl content, and precipitation occurs in the aqueous phase. After modification with an excessive amount of modifier, the hollow silica still has poor compatibility with organic solvents and precipitation occurs.
[0113] From the comparison of Examples 1-8 and Comparative Examples 3-5, it can be seen that when the aging time and temperature exceed the range, the hollow silica particles will agglomerate and cannot be subsequently modified and phase-changed. If the aging is not performed or the silanol content on the surface of the hollow silica nanoparticles after aging is too high, the modified hollow silica will have poor compatibility with organic solvents and produce precipitation.
[0114] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Hollow silica nanoparticles, characterized in that: The average hollow rate of the hollow silicon dioxide nanoparticles is 50%-70%, the average particle diameter is 20-80nm, and the percentage of hydroxyl groups on the surface of the nanoparticles is 16%-25%.
2. The method for preparing hollow silica nanoparticles according to claim 1, characterized in that: The method comprises the following steps: fully mixing an organosilicon source, a surfactant, an expansion agent, a catalyst and an organic solvent, heating the mixture to complete the reaction, and obtaining a silane polymer solution; in the presence of a catalyst, subjecting the silane polymer solution to a mineralization reaction, and centrifugally washing the mixture to obtain hollow silica primary particles; and then mixing the hollow silica primary particles with water, heating and aging the mixture to obtain a stable and precipitate-free aqueous hollow silica secondary particle dispersion.
3. The preparation method according to claim 2, characterized in that: Also includes: Post-treating the obtained stable and precipitate-free aqueous hollow silica secondary particle dispersion; Preferably, the post-treatment comprises: uniformly mixing the aqueous hollow silica secondary particle dispersion, propylene glycol methyl ether acetate and a silane coupling agent, and performing modification at 50-70° C. to obtain a stable and precipitate-free oil-based hollow silica secondary particle dispersion, wherein: the silane coupling agent comprises at least one of 3-(methacryloyloxy)propyltrimethoxysilane, KH570 and KH550; Preferably, the post-treatment comprises: separating and washing the aqueous hollow silica secondary particle dispersion, and adjusting the solid content of the dispersion to 5-20% to obtain a hollow silica nanoparticle dispersion; Preferably, the post-treatment comprises: drying the aqueous hollow silica secondary particle dispersion to obtain hollow silica nanoparticle powder.
4. The preparation method according to claim 2, characterized in that: The silane polymer solution is prepared by the following method: at room temperature, a surfactant, a swelling agent and a catalyst are placed in an organic solvent and stirred evenly to obtain a modifier solution; then an organic silicon source is added to the modifier solution, and after heating and reaction is complete, a silane polymer solution is obtained; Preferably, the surfactant has an HLB value of ≥10 and contains one or more hydroxyl groups. Preferably, the surfactant comprises at least one of a hydroxyl-containing triblock polymer and a hydroxyl-containing nonionic surfactant, more preferably at least one of F108, F127, and polyethylene glycol; Preferably, the expansion agent includes at least one of toluene and trimethylbenzene; Preferably, the catalyst comprises at least one of acetic acid, hydrochloric acid, hydrofluoric acid, ammonia water, and sodium hydroxide; Preferably, the organic solvent includes at least one of methanol, ethanol, isopropanol, acetone, methyl butyl ketone, methyl isobutyl ketone, and propylene glycol methyl ether acetate; Preferably, the organic silicon source includes at least one of tetramethoxysilane, vinyltriethoxysilane, 3-aminopropyltrimethoxysilane and fluorine-containing silane.
5. The preparation method according to claim 4, characterized in that: The heating reaction temperature is 70°C-100°C and the time is 1h-6h.
6. The preparation method according to claim 2, characterized in that: The preparation of the hollow silica primary particles comprises: removing impurities from the silane polymer solution, mixing it evenly with a dispersant, adding a catalyst to carry out a mineralization reaction, and centrifuging and washing to obtain hollow silica primary particles; Preferably, the impurity removal of the silane polymer solution comprises: removing impurities generated in the heating reaction of the silane polymer solution by atmospheric distillation or reduced pressure distillation; Preferably, the dispersant includes at least one of water, water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide, guar gum, and polyethylene glycol esters of fatty acids; Preferably, the catalyst includes at least one of acetic acid, hydrochloric acid, hydrofluoric acid, ammonia water, and sodium hydroxide.
7. The preparation method according to claim 6, characterized in that: The mass ratio of the silane polymer in the silane polymer solution to the dispersant is 1:30-1:5, and the mass ratio of the silane polymer to the catalyst is 10:1-2:
1.
8. The preparation method according to claim 2, characterized in that: The preparation of the hollow silica secondary particle dispersion comprises: uniformly mixing the hollow silica primary particles and water, and heating and ripening to obtain the hollow silica secondary particle dispersion with a hydroxyl content of 16%-25%.
9. The preparation method according to claim 8, characterized in that: The heating and aging temperature is 150℃-240℃, and the time is 30h-40h.
10. An antireflection film, characterized in that The hollow silica nanoparticles are prepared by using the hollow silica nanoparticles described in claim 1 or the preparation method described in any one of claims 2 to 9.